2016
DOI: 10.1186/s40168-016-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of faecal microbiota in Blastocystis-positive and Blastocystis-negative irritable bowel syndrome patients

Abstract: BackgroundWe investigated whether the carriage of Blastocystis in IBS patients was associated with differences in the faecal microbiota. Forty patients with diarrhoea-predominant IBS (26 Blastocystis-positive and 14 Blastocystis-negative) and 57 healthy controls (HC) (42 Blastocystis-positive and 15 Blastocystis-negative) submitted faecal samples for metataxonomic analysis of the 16S ribosomal RNA gene. Differences in the relative abundance of bacteria in these IBS and HC groups were evaluated from phylum to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 35 publications
4
63
1
1
Order By: Relevance
“…Scrutinizing the linkage of microbial signature with the IBS subtype, varied results have been reported across studies 26 , a reduced microbial diversity and increased F/B ratio were more frequently found. 45 47 48 Our study did find an increased F/B ratio in this IBS-D cohort, but with no difference in the microbial richness. Notably, proportions of taxa were significanlty altered shown in BA + IBS-D patients, not in all IBS-D population, illustrating abnormal BA excretion closely related to differentiation of gut microbiota among the IBS-D population.…”
Section: Discussioncontrasting
confidence: 45%
“…Scrutinizing the linkage of microbial signature with the IBS subtype, varied results have been reported across studies 26 , a reduced microbial diversity and increased F/B ratio were more frequently found. 45 47 48 Our study did find an increased F/B ratio in this IBS-D cohort, but with no difference in the microbial richness. Notably, proportions of taxa were significanlty altered shown in BA + IBS-D patients, not in all IBS-D population, illustrating abnormal BA excretion closely related to differentiation of gut microbiota among the IBS-D population.…”
Section: Discussioncontrasting
confidence: 45%
“…S3C). Compared with healthy individuals, a higher F/B ratio has also been observed in patients with irritable bowel syndrome (IBS), hypertension, autism, and chronic fatigue syndrome in case control studies [20][21][22][23]. Taken together, these comparisons above suggest that cancer treatments may not significantly disrupt the patients' individual signatures of gut microbiota; however, the cancer patients have distinct gut microbiota features compared to the healthy cohort.…”
Section: Limited Impact Of Cancer Therapy On Individual Gut Microbiotamentioning
confidence: 92%
“…At phylum level, Firmicutes and Fusobacteria decreased signi cantly, and Proteobacteria increased signi cantly in IBS-D patients. In reviewing the literature, decreased levels of Firmicutes and increased levels of Bacteroidetes were found in 2 studies [20,21], one in China, but 4 studies [22,23,24,25] reported opposite results, and 3 studies [24,25,26] found that Proteobacteria were increased. In assessing genus level, Enterobacteriaceae signi cantly increased, and Alloprevotella, Fusobacterium signi cantly decreased.…”
Section: The Composition Of Gut Microbiota In Ibs-d Patients Was Abnomentioning
confidence: 99%